Magnetospheric and ionospheric vortices response to negative solar wind dynamic pressure pulse - Zhao, Huayu; Yang, Huigen; Hu, Zejun; Huang, Dehong; Li, Bin; Zhang, Beichen; Liu, Jianjun (Frontiers in Astronomy and Space Sciences, 2025)
In this work, we present two individual cases showing that a negative solar wind dynamic pressure pulse can lead to magnetospheric decompression and generate a clockwise vortex in the duskside magnetosphere. In response to this decompression, a magnetospheric vortex in the duskside sector was observed by the Time History of Events and Macroscale Interactions during Substorms (THEMIS) mission. Minimum variance analysis (MVA) of the mass flux, together with the corresponding equivalent ionospheric currents (EICs), indicates that the magnetospheric vortex rotated clockwise which is opposite to the typical direction of vortices induced by positive solar wind dynamic pressure pulses. The associated clockwise EICs vortex suggests that the magnetospheric vortex was connected to the ionospheric vortex via downward field-aligned currents (FACs). Time series analysis of the EICs further reveals that the vortex propagated eastward, consistent with the tailward motion of the magnetospheric vortex. Moreover, the occurrence of the clockwise EIC vortex at lower latitudes, together with the THEMIS satellite location, indicates that the magnetospheric vortices associated with traveling convection vortices (TCVs) are generated not at the magnetopause, but within the nightside magnetosphere.